Factors that influence job satisfaction among employees of manufacturing company in Penang - Pavitra, Kunjikanan (2021)
Job satisfaction is one of the most significant topics to address in today's workplace. Most companies are able to meet their organizational goals by enhancing employee job satisfaction. At the same time, some organizations continue to overlook employee job satisfaction. As a result of this situation, employers may find it difficult to compete and stay afloat in the corporate sector. Malaysia's economy relies heavily on manufacturing companies. Job satisfaction is crucial in achieving the firm's goals and objectives. Employee work satisfaction is influenced by several factors, according to the researchers. Because there is a significant drop in job satisfaction among manufacturing employees, the researcher has chosen Penang as the location for this study. The study focuses on the elements that influence job satisfaction among employees of a manufacturing firm in Penang. This study looked at influencing elements such working condition, compensation and benefit, and training and development to see if there was a link between those factors and job satisfaction among employees in manufacturing enterprises in Penang. Questioners were distributed to a random manufacturing firm in Penang to collect data. SPSS was used to gather and analyze data gathered. In a manufacturing firm in Penang, Malaysia, the working condition factor has been found as the most important contributor to employee job satisfaction. Employee compensation and benefit and training and development were found to have a substantial link with job satisfaction among employees of a manufacturing firm in Penang.